“It is not fun to read, unless it is something interesting”: A convergent mixed methods study on the alignment of current research and pupils’ perception of their reading habits - Amble, Nora Mikkelsen; Våg, Signe Merethe Næss (UiT Norges arktiske universitet, 2024)
This study examines the correlation between current reading research and pupils’ perception of their own reading habits. Our thesis questions are: To what extent do current research and mapping align with lower secondary pupils’ perceptions of their reading habits? How can we use our findings to aid future reading instruction in English? Using a convergent mixed methods design our thesis questions were investigated through a literature review and a cross-sectional questionnaire. To identify literature for the review we utilized several databases and search terms. We deemed 17 articles important for answering our thesis questions. We recruited 53 lower secondary pupils as respondents to our questionnaire. Our respondents’ parishes to one rural and one urban school in Troms and Finnmark. In the questionnaire they were asked a number of questions regarding their reading attitudes, habits and motivation. Pupils were given a mix of close- and open-ended questions. Through our research, we found that mapping projects such as PISA and PIRLS indicate that Norwegian pupils’ reading comprehension, reading motivation and joy of reading are on a declining trend. Results from our review share similar findings where pupils have low reading value and negative reading attitudes. Results from the questionnaire complements the findings from the review. While most pupils had a neutral stance on reading, they expressed low reading motivation. To answer the final thesis question, based on results from the literature review and the questionnaire, we make some recommendations on how to promote joy of reading and spark reading engagement in the classroom.